Language and conquest in early modern Ireland : English Renaissance literature and Elizabethan imperial expansion - Palmer, Patricia, 1957- (Cambridge University Press, 2001)
The Elizabethan conquest of Ireland sparked off two linguistic events: it initiated the language shift from Irish to English, which constitutes the great drama of Irish cultural history, and it marked the beginnings of English linguistic expansion. Palmer explores the role of language in shaping colonial ideology and English identity.